Pencapaian Target Sustainable Development Goals dengan Konsep Material Flow Cost Accounting - Dianah Afifah; Novita Novita (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2021)
This study aims to support achievement of the SDGs target with MFCA concept, by involving dapure bunda Depok as the study object. Methods of analysis in this study are using qualitative descriptive. Based on the analysis carried out through the data obtained, the production activities have not yet reached optimization. The results of this analysis show 84,4% of production input are positive output, while 15,6% are negative output in the research model 1, and 88,1% of production input are positive output, while 11,9% are negative output in the research model 2. This research provides improvement in the stages final of implementing MFCA which is in line with achieving the SDGs target, and optimization as to increase profits and reduce environmental impact.